Beliefs about managing dental problems among older people and dental professionals in Southern Brazil. Issue 2 (13th December 2018) - Goulart, Mariél de Aquino; De Marchi, Renato José; Padilha, Dalva Maria P.; Brondani, Mario A.; MacEntee, Michael I.
Abstract: Objectives: To explore the sociocultural context in which patients and dentists in urban and rural communities in Southern Brazil interpret dental problems. Method: Beliefs and experiences related to dental problems were explored in eight focus groups involving a total of 41 older patients, and in direct interviews with two dentists and two dental assistants. The interactions were audio recorded and transcribed for thematic analysis. Results: The beliefs and experiences of the participants focused on four main themes: cultural beliefs; dental services; decisions to extract teeth; and expectations for change. A culture of pre‐nuptial tooth loss and complete dentures was considered beneficial to young women. Although dental services at the time were scarce in the region, demands for relief of pain were extensive despite the fear and anxiety of the participants. Extraction of teeth and fabrication of complete dentures were the usual dental treatments available, although some participants felt that dentists withheld other treatment options. Participants were hopeful that dental services would improve for their children. Conclusions: Patients and dental professionals in urban and rural communities of Southern Brazil managed dental problems within a culture of limited access and availability of services that favoured dental extractions and complete dentures.